2014
DOI: 10.1186/2055-0391-56-4
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and body organ characteristics of broilers supplemented with dietary sodium and sodium salts under a phase feeding system

Abstract: The effect of sodium and sodium salts on carcass and body organ characteristics of broilers under a four phase feeding program were investigated. A basal diet (0.08% dNa with NaCl) was formulated and one of two sources of dNa (NaHCO3 and Na2SO4) were supplemented to obtain four different percentages of dNa (0.17, 0.26, 0.35, and 0.44%) for each treatment. There was a linear decrease in dressing percentage (DP) with source × level interaction (p ≤ 0.001), while there was a linear increase in breast yield and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In this regards, Mc Dowell (2003) postulated 29 elements known to be required by at least one animal species. Mushtaq et al (2014) reported that Na + , for example, is the principal cation of extracellular fluids that are involved in numerous functions including the regulation of acid base balance and the absorption of amino acids and glucose that are essential for body growth, which may explain the significant improvement in growth performance of broiler chickens obtained from the present experiment, as Na + is one of the several elements found in the chemical composition of clay minerals. On the other hand, the interest in using nanotechnology as a new advanced tool in broiler nutrition indicates that nanoscale particles have chemical and physical properties that completely differ from those of large-scale particles (Ramirez-Mella & Hernandez-Mendo 2010).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this regards, Mc Dowell (2003) postulated 29 elements known to be required by at least one animal species. Mushtaq et al (2014) reported that Na + , for example, is the principal cation of extracellular fluids that are involved in numerous functions including the regulation of acid base balance and the absorption of amino acids and glucose that are essential for body growth, which may explain the significant improvement in growth performance of broiler chickens obtained from the present experiment, as Na + is one of the several elements found in the chemical composition of clay minerals. On the other hand, the interest in using nanotechnology as a new advanced tool in broiler nutrition indicates that nanoscale particles have chemical and physical properties that completely differ from those of large-scale particles (Ramirez-Mella & Hernandez-Mendo 2010).…”
Section: Discussionmentioning
confidence: 54%
“…Recently published data indicated that Ag-nanoparticles affected gene expression for muscle growth directly or indirectly, fibroblast growth factor 2 (FGF2), vascular endothelial growth factor (VEGF) and Na + /K + transporting ATPase (Hotowy et al 2012;Sawors et al 2013), which may explain the positive effect of nanoclay minerals used in the present experiment, as this clay contains several minerals in its composition such as Na + , K + and Ca ++ , which can enhance internal organs' percentage and increase BW and BWG obtained from our experiment but with nanoclay minerals. Mushtaq et al (2014) demonstrated that Na + , the principal cation of extracellular fluid, is involved in numerous functions including the regulation of acid base balance and the absorption of glucose and amino acids that also play a particular role in improving internal organs' percentage when it is transferred into nanoparticles. Sawors et al (2013) proposed that muscle cell number is related to genetic, environmental and nutritional factors including structural and energy provided molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors did not find any difference between sodium bicarbonate and Na 2 SO 4 (Mushtaq et al, 2014(Mushtaq et al, , 2013 or between sodium bicarbonate and sodium chloride (Murakami et al, 2000) on growth performance from 1-42 d of age, Murakami et al, (1997) showed that supplying dietary sodium levels by sodium chloride improves the FCR compared to that supplied by sodium bicarbonate.…”
Section: Re Sults and Discussionmentioning
confidence: 93%
“…It seems that supplying the requirement of 0.23% sodium, which obtained from the lowest level of either sodium bicarbonate (i.e., 0.26%) or sodium chloride (i.e., 0.18%), was adequate to improve the FCR during 1–38 d of age. However, Murakami et al, (), Murakami et al, () and Mushtaq et al, (), Mushtaq et al, () found that supplying sodium concentration more than 0.15%–0.17% does not lead to further production advantages. Although some authors did not find any difference between sodium bicarbonate and Na 2 SO 4 (Mushtaq et al, , ) or between sodium bicarbonate and sodium chloride (Murakami et al, ) on growth performance from 1–42 d of age, Murakami et al, () showed that supplying dietary sodium levels by sodium chloride improves the FCR compared to that supplied by sodium bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation